Pesquisa de resíduos de pesticidas organoclorados no leite distribuído a população de Fortaleza (CE.) - Araújo, Lúcia de Fátima Pereira (1984)
This study was to measure organochlorine pesticide residues in bovine milk in Fortaleza, Ce., in Northeast Brazil. [...]